Kaposi's sarcoma-associated herpesvirus (KSHV) gB dictates a low-pH endocytotic entry pathway as revealed by a dual-fluorescent virus system and a rhesus monkey rhadinovirus expressing KSHV gB. - Shanchuan Liu; Sarah Schlagowski; Anna K Großkopf; Natalia Khizanishvili; Xiaoliang Yang; Scott W Wong; Elina M Guzmán; Marija Backovic; Stefano Scribano; Arne Cordsmeier; Armin Ensser; Alexander S Hahn (PLoS Pathogens)
Interaction with host cell receptors initiates internalization of Kaposi's sarcoma-associated herpesvirus (KSHV) particles. Fusion of viral and host cell membranes, which is followed by release of the viral capsid into the cytoplasm, is executed by the core fusion machinery composed of glycoproteins H (gH), L (gL), and B (gB), that is common to all herpesviruses. KSHV infection has been shown to be sensitive to inhibitors of vacuolar acidification, suggestive of low pH as a fusion trigger. To analyze KSHV entry at the single particle level we developed dual-fluorescent recombinant KSHV strains that incorporate fluorescent protein-tagged glycoproteins and capsid proteins. In addition, we generated a hybrid rhesus monkey rhadinovirus (RRV) that expresses KSHV gB in place of RRV gB to analyze gB-dependent differences in infection pathways. We demonstrated lytic reactivation and infectivity of dual-fluorescent KSHV. Confocal microscopy was used to quantify co-localization of fluorescently-tagged glycoproteins and capsid proteins. Using the ratio of dual-positive KSHV particles to single-positive capsids as an indicator of fusion events we established KSHV fusion kinetics upon infection of different target cells with marked differences in the "time-to-fusion" between cell types. Inhibition of vesicle acidification prevented KSHV particle-cell fusion, implicating low vesicle pH as a requirement. These findings were corroborated by comparison of RRV-YFP wildtype reporter virus and RRV-YFP encoding KSHV gB in place of RRV gB. While RRV wt infection of receptor-overexpressing cells was unaffected by inhibition of vesicle acidification, RRV-YFP expressing KSHV gB was sensitive to Bafilomycin A1, an inhibitor of vacuolar acidification. Single- and dual-fluorescent KSHV strains eliminate the need for virus-specific antibodies and enable the tracking of single viral particles during entry and fusion. Together with a hybrid RRV expressing KSHV gB and classical fusion assays, these novel tools identify low vesicle pH as an endocytotic trigger for KSHV membrane fusion.